Development of E-Modules Containing the Quran and Hadith to Increase Student Motivation - Kusuma, Lukman W; Mastuang, Mastuang; Dewantara, Dewi (Universitas Lambung Mangkurat, 2022)
An electronic module with motivational content from the verses of the Quran and Hadith designed through the teaching of Discovery Learning with Linear Impulse and Momentum material is not yet available. This research and development aim to produce e-modules containing verses from the Qur'an and Hadith that are suitable for use in learning. This research aims to describe the validity, practicality, and effectiveness of e-modules containing verses from the Qur'an and Hadith. This study uses the ADDIE development model with the subject of an e-module trial containing verses from the Koran and Hadith, which was tested on ten students of class X MIPA 1 MA Negeri 1 Banjarmasin. Data collection techniques were carried out through interviews, questionnaires, and tests. Data analysis was carried out through the percentage validity test, the average score of the response questionnaire, the learning outcomes test and the ARCS motivation questionnaire. The results showed that: 1) The validity of the e-module got a score of 84.88%, which was categorized as very high with a reliability of 0.97, 2) The practicality of the e-module got 78.71% which was categorized as practical, 3) The effectiveness of getting an N score-gain of 0.79 with a high category 4) Students' learning motivation gets an N-gain score of 0.52 which is categorized as moderate. It was concluded that the e-module containing the verses of the Qur'an and Hadith was suitable for use in learning